INCREASING ENGLISH LANGUAGE KNOWLEDGE FROM READING COMPREHENSION EXERCISES (World Bulletin of Social Sciences, 2024)
Reading comprehension skills that allow students to process others’ writing so they can understand underlying messages and make insightful connections. These skills are extremely important for students’ successful development. Learning interactive and fun methods for helping students engage with their educational advancements